A Laboratory Diet-Overlay Bioassay to Monitor Resistance in Lygus lineolaris (Hemiptera: Miridae) to Insecticides Commonly Used in the Mississippi Delta. Issue 4 (13th July 2020) - Portilla, Maribel
Abstract: A laboratory, diet-overlay pesticide bioassay was developed using a susceptible population of the tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), to study its susceptibility to neonicotinoid, sulfoxamine, organophosphate, and pyrethroid insecticides (thiamethoxam, sulfoxaflor, acephate, and permethrin, respectively). The diet-overlay bioassay was compared to the traditional glass-vial surface residue bioassay. We measured LC50 values by feeding tarnished plant bug adults known doses of insecticides dispensed on top of diet in a 10% solution of honey water for thiamethoxam and 10% acetone in water solutions for permethrin, acephate, and sulfoxaflor. Both the diet-overlay and glass-vial bioassays used dose-response (mortality) regression lines to calculate LC50 values for each insecticide at 6-, 24-, 48-, and 72-h post-exposure. Data variability from the glass-vial bioassay was higher for permethrin, sulfoxaflor, and thiamethoxam than the diet-overlay bioassay, for all evaluation times. In contrast, there was lower variability among replicates to acephate in the glass-vial assay compared to the diet-overlay assay. Control mortalities observed on diet-overlay bioassay were lower (0–5%) than those observed on the glass-vial bioassay (4–27%). The use of green beans, floral-foam, rolling glass vials, and insect handling made the existing standard method tedious to manipulate and difficult to handle large numbers of individuals. The nonautoclaved solid diet provides an opportunity to significantly reduce cost and variability associated with procedures of other bioassay methods. In general, the baseline data provide a basis for future comparison to determine changes in resistance over time.